Management of Autoimmune Hepatitis - Supriono Supriono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Autoimmune hepatitis (AIH) is a necroinflammatory liver disease of unknown etiology. Although the pathogenetic mechanism of AIH is still unknown, an underlying genetic predisposition and the association of the disease with certain human leukocyte antigens (HLAs) have been suggested. The molecular mimicry has been proposed as a pathogenetic mechanism for AIH. The diagnosis of AIH is based on a constellation of clinical, serological, and histopathological findings. The International Autoimmune Hepatitis Group (IAIHG) proposed diagnosis criteria in 1993, which were revised in 1999. In 2008, the IAIHG decided to devise a simplified scoring system for wider applicability in routine clinical practice. Based on clinical and serological parameters, AIH cases have been categorized into three subtypes: type-1 AIH, type-2 AIH and type-3 AIH. The therapeutic guidelines of AIH include immunosuppressive agent with corticosteroid and usually in combination with azathioprine. Starting dose of prednisone monotherapy is 60 mg daily, which should be tapered slowly over a 1 week period to a maintenance dose of 20 mg daily. The other regimen is used in combination with azathioprine, prednisone dose is started at 30 mg and tapered 10 to 5 mg every week until a maintenance dose of 10 mg is achieved. Azathioprine is given at the dose of 50 mg daily. In the very few patients that do not tolerate or have significant side effects to gold standard therapy, alternative immunosuppressive drugs should be given. Other powerful immunosuppressive drugs and molecular interventions are being developed based on recent insights into pathogenic pathways, emerging pharmacologic agents, and new technologies. Keywords: autoimmune hepatitis, pathogenesis, diagnosis, management